EVALUASI KINERJA DIREKTORAT BELA NEGARA DALAM SOSIALISASI KESADARAN BELA NEGARA (STUDI di DIT BELA NEGARA) - , R. AGUS LISTYOWARNO, Prof. Dr. Djoko Soerjo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study was designed to gain an understanding of the Performance Evaluation of State-Defense Awareness Dissemination (Studies in the State Directorate of Defense). Research objectives are: 1). To determine the level of achievement of performance targets in support of the State Directorate of Defense socialization defend the state of consciousness, 2). To find out what are the barriers that can interfere with socialization to defend the state of consciousness, 3). To determine the level of achieving success in the performance of the State Directorate of Defense held a dissemination awareness to defend the country. Methods of research using this type of research carried out by using descriptive method with qualitative approach. A qualitative approach is performed to find out more about the information of the respondents are more aware of the condition of socialization defend the country that have been implemented by the State Directorate of Defense. In this study uses data collection techniques are performed by means of: a. Deployment questionnaire. Data collection is done by spreading questionnaire. b. Interview. Interviews were conducted to obtain information more widely and more deeply that are not encased in a list of questions on the document and questionnaire. c. Documentation. Data retrieval personnel and activities of the State Directorate of Defense program and budget In evaluating the dissemination activities to defend the state of consciousness in the State Directorate of Defense, the researchers will conduct a survey of the work program and budget of the State Directorate of Defense personnel and achievement of performance objectives the State Directorate of Defense. State Directorate of Defense budget conditions in the dissemination of defending the country is very minimal, with the lack of a budget then the intensity of the work program to be limited, so the out put of socialization is not a lot of cadres to defend the country, therefore it needs an effort to increase the nominal amount and intensity of program budget work in the socialization of awareness to defend the country. In the Directorate of Defense personnel performance measurement state actors found a decrease in the performance of personnel. The study found: first, information about how the performance of the State Directorate of Defense in particular in the work program and budget and performance levels of the Directorate of Defense personnel in carrying out the State to defend the state of consciousness socialization and second, to know the factors inhibiting the performance of the State Directorate of Defense in disseminating awareness to defend the country